Calcium and Phosphor Intake in Preterm Infants: Sensitivity and Specifity of 6-Hour Urine Samples to Detect Deficiency - Mihatsch, W.; Trotter, A.; Pohlandt, F. (Klinische Pädiatrie, 2012)
Aim of the present study was to test whether six-hour (6 h) urine specimens predict the 24-hour (24 h) mineral homeostasis in individual infants born preterm. Urinary Calcium (Ca) and Phosphate (P) concentrations were studied in 60 stable infants; gestational age 34 (25–42) weeks. In 58 infants four 6 h urine specimens and in 2 infants all spot urine specimens obtained within 24 h were analyzed. In 39 infants born preterm coefficients of variation were 0.42 (SD 0.26) and 0.41 (SD 0.26) for Ca and P measurements in the four 6 h urine specimens obtained within 24 h, respectively, The mineral homeostasis of the infants was defined as Ca or P surplus homeostasis if the 24 h urinary concentrations were ≥1 mmol/l. The sensitivity, specificity, and PPV of a 6 h urinary specimen to predict Ca deficiency homeostasis (24 h urinary Ca <1 mmol/l) were 0.93 (0.77–0.98; 95%CI), 0.72 (0.43–0.90) and 0.90 (0.74–0.96). The sensitivity, specificity and PPV for urinary P were 0.8 (0.38–0.96), 0.97 (0.85–0.995), and 0.8 (0.38–0.96). In conclusion, in infants born preterm on regular 3 or 4 h feedings, 6 h urine sampling is sufficiently precise for prediction of Ca and P mineral deficiency homeostasis (PPV 0.92 and 0.83). However, measurements at regular intervals (twice weekly) are recommended not to miss any infant in mineral deficiency homeostasis.
Keywords: infants born preterm; supplementation; calcium; phosphate; monitoring; bone mineral deficiency; osteopenia; urine